2013
DOI: 10.1016/j.chom.2013.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Fusobacterium nucleatum Potentiates Intestinal Tumorigenesis and Modulates the Tumor-Immune Microenvironment

Abstract: SUMMARY Increasing evidence links the gut microbiota with colorectal cancer. Metagenomic analyses indicate that commensal Fusobacterium spp. are associated with human colorectal carcinoma but whether this is an indirect or causal link remains unclear. We find that Fusobacterium spp. are enriched in human colonic adenomas relative to surrounding tissues and in stool samples from colorectal adenoma and carcinoma patients compared to healthy subjects. Additionally, in the ApcMin/+ mouse model of intestinal tumori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

85
2,046
10
22

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 2,085 publications
(2,163 citation statements)
references
References 42 publications
85
2,046
10
22
Order By: Relevance
“…is pro‐inflammatory, exhibits adhesive and invasive properties via virulence factors (i.e., FadA, fusobacterium autotransporter protein 2 and fusobacterial outer membrane protein A), and promotes pro‐oncogenic features which might contribute to accelerated tumor growth and tumor burden 38, 47, 54. Increased Fusobacterium nucleatum is associated with an increase in adenoma formation and accelerated small intestinal adenocarcinoma development in rodent models of GI neoplasia 41. Coupled with this was an expansion of CD11b + myeloid cells (i.e., dendritic cells, macrophages, and myeloid‐derived suppressor cells) in the neoplastic tissues and an NF‐κB‐driven pro‐inflammatory response 41.…”
Section: Discussionmentioning
confidence: 99%
“…is pro‐inflammatory, exhibits adhesive and invasive properties via virulence factors (i.e., FadA, fusobacterium autotransporter protein 2 and fusobacterial outer membrane protein A), and promotes pro‐oncogenic features which might contribute to accelerated tumor growth and tumor burden 38, 47, 54. Increased Fusobacterium nucleatum is associated with an increase in adenoma formation and accelerated small intestinal adenocarcinoma development in rodent models of GI neoplasia 41. Coupled with this was an expansion of CD11b + myeloid cells (i.e., dendritic cells, macrophages, and myeloid‐derived suppressor cells) in the neoplastic tissues and an NF‐κB‐driven pro‐inflammatory response 41.…”
Section: Discussionmentioning
confidence: 99%
“…117 Two European studies demonstrate associations between sulfidogenic bacteria (Fusobacterium spp.) and the tumor surface in a subset of CRC 118,119 Indeed, the Gaskins' lab demonstrated that sulfide is genotoxic at doses found in the colon providing a reasonable explanation for these observations. [120][121][122][123] The rationale for this hypothesis is also supplemented by our long-term study of mammalian cell responses to the effects of exogenous sulfide.…”
mentioning
confidence: 99%
“…F. nucleatum is a highly invasive, gram-negative anaerobic bacterium and part of the oral and gut commensal microbiota that has been linked to several diseases, such as appendicitis (16) and inflammatory bowel disease (17). This bacterium may contribute to colorectal cancer development by invading colonic mucosa and inducing local inflammation and increased expression of cytokines, leading to colorectal disease (18). More convincing evidence that F. nucleatum infection directly contributes to colorectal carcinogenesis rather than being a consequence of disease progression derives from two recent reports showing that F. nucleatum invasion, through its unique FadA adhesion, recruits tumor-infiltrating immune cells and generates an oncogenic/proinflammatory microenvironment conducive for colorectal neoplasia (18,19).…”
Section: The Colon Cancer Microbiome In the Context Of Human Intralummentioning
confidence: 99%
“…This bacterium may contribute to colorectal cancer development by invading colonic mucosa and inducing local inflammation and increased expression of cytokines, leading to colorectal disease (18). More convincing evidence that F. nucleatum infection directly contributes to colorectal carcinogenesis rather than being a consequence of disease progression derives from two recent reports showing that F. nucleatum invasion, through its unique FadA adhesion, recruits tumor-infiltrating immune cells and generates an oncogenic/proinflammatory microenvironment conducive for colorectal neoplasia (18,19). The importance of this bacterium to colorectal cancer has also been demonstrated in a recent European human cohort study in which F. nucleatum has been identified as a novel risk factor for disease progression from adenoma to cancer (20).…”
Section: The Colon Cancer Microbiome In the Context Of Human Intralummentioning
confidence: 99%